First Nations pictograph drawing of prisoners guarded by dogs (1947)
Famous Keremeos drawing of prisoners guarded by dogs. Note from photo: [Indian Pictograph - Brohley Cr. Park Area C. 1947. Frank Martin. White Rock, B.C]. Accession no. 1524.